1991
DOI: 10.1577/1548-8640(1991)053<0195:uoefcf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Fish Counters for Coho and Chinook Salmon, Steelhead, and Cutthroat Trout Smolts

Abstract: Electronic fish counters produce accurate counts, are less stressful to fish, and require fewer personnel than traditional methods of counting smolts of coho salmon (Oncorhynchus kisutch), chinook salmon (O. tshawytscha), steclhead (O. mykiss), and sea-run cutthroat trout (O. clarki) released from hatcheries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Each volitional‐release pond was equipped with an FC‐3 electronic fish counter (Northwest Marine Technology, Shaw Island, Washington). The counter enumerated fish bidirectionally, and the total number of fish leaving was determined by subtracting upstream from downstream migrants (Appleby and Tipping 1991). The outlet of the volitional‐release pond was modified so fish could return to the pond if they desired; otherwise, the fish moved over dam boards into the sump and down the pond drain.…”
Section: Methodsmentioning
confidence: 99%
“…Each volitional‐release pond was equipped with an FC‐3 electronic fish counter (Northwest Marine Technology, Shaw Island, Washington). The counter enumerated fish bidirectionally, and the total number of fish leaving was determined by subtracting upstream from downstream migrants (Appleby and Tipping 1991). The outlet of the volitional‐release pond was modified so fish could return to the pond if they desired; otherwise, the fish moved over dam boards into the sump and down the pond drain.…”
Section: Methodsmentioning
confidence: 99%
“…Fundamental mechanisms and phenomena underlying electrical impedance measurements for fish detection in freshwater were described in a recent study (Nowak and Lankheet 2022). The introduced approach extended the concept of the so-called resistivity fish counters used in stock estimation in flowing waters and in aquaculture (Appleby and Tipping 1991, Smith et al 1996, Li et al 2021. Flatfish detection in a marine environment, however, presents a broad range of different challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Reddin et al [ 7 ] reported perfect agreement between Atlantic salmon counts during a 26 day long test conducted in a Canadian river. Appleby and Tipping [ 8 ] tested counting efficiency of a commercial resistivity counter for different fish species stocked at rearing ponds, comparing the readings to results of hand counts. They found the mismatch to be within 1,4% to 7%, depending on the counting rate.…”
Section: Introductionmentioning
confidence: 99%